The association between the dietary inflammatory index and allergic rhinitis: a case–control study - Wang, Qian; Dong, Niuniu; Feng, Yan; Ning, Yan; Zhu, Ruifang; Han, Shifan (Frontiers in Nutrition, 2024)
Background and Objective: Allergic rhinitis (AR) is a common chronic inflammatory disease that significantly impacts the quality of life of patients. However, there is limited research on the relationship between the Dietary Inflammatory Index (DII) and the risk of AR. Our study aimed to assess the association between DII and AR in a sample of adults from North China.Methods: In a case-control study, we selected 166 cases of AR and 166 age-and gender-matched controls. Dietary intake was assessed using a validated food frequency questionnaire. The energyadjusted DII (E-DII) scores were calculated based on the quantity of diet components with inflammatory or anti-inflammatory potential. We used conditional logistic regression models to examine the association between E-DII and AR.Results: Our findings indicate a positive correlation between E-DII and AR risk. After controlling for confounders, individuals in the highest E-DII tertile exhibited a 4.41-fold increased risk of AR compared to those in the lowest tertile (OR 4.41,. Additionally, stratified analysis showed that E-DII was positively associated with AR subtype (seasonal vs. perennial), duration (≤6 years vs. >6 years), severity (mild vs. moderate-severe), and onset time (intermittent vs. persistent). Furthermore, individuals in the highest E-DII tertile had higher intake of total fat, SFA, PUFAs, and n-6 PUFAs.In conclusion, we realized that there is a positive association between the E-DII score and AR. The consumption of diets abundant in anti-inflammatory nutrients and low in proinflammatory nutrient contents is recommended as a preventative strategy against AR.